The impact of persistent anomalous precipitation in Southwest China caused by low-frequency atmospheric disturbances in different latitudes and altitudes - Xiao, Tian-Gui; Huang, Yao; Han, Lin; Nong, Ya-yue (Frontiers in Earth Science, 2023)
In this paper, the low-frequency characteristics of persistent extreme precipitation in Southwest China and the characteristics of Atmospheric Low-Frequency Oscillation in different latitudes and altitudes affecting precipitation were discussed by synthetic analysis and Butterworth filtering with precipitation data from meteorological stations and NCEP/NCAR reanalysis data. The configuration relationship of low-frequency systems in three-dimensional space and its influence on the persistent extreme precipitation in southwest China were shown, which provided a theoretical basis for the forecast of the extended period of persistent abnormal precipitation in southwest China. The results showed that: (1) In the low-frequency circulation filed, the Ural Mountains, east of Lake Baikal, the Sea of Okhotsk-Japan, the Western Pacific subtropical high control area, the South China Sea, the Indian Peninsula and the Bay of Bengal were the key areas affecting precipitation. (2) The oscillation coule better reflects the original circulation characteristics at all latitudes of each layer, that is, on 15-30 day of oscillation will afect precipitation at all altitudes and latitudes. (3) In the 15-30 day low-frequency circulation field, at the lower level, different low-frequency cyclones and anticyclones moved to the mid-latitude, bringing cold air to the South and warm air to the north, and converge in different forms in the precipitation area. In the middle layer, the low-frequency high-pressure centers and the low-pressure centers in the middle and high latitudes move southward, finally forming a circulation situation of High West and low east. At the upper level, the rainy area was controlled by low-frequency anticyclone and divergence centers from different regions, forming high-altitude divergence field.